2022
DOI: 10.1167/jov.22.8.14
|View full text |Cite
|
Sign up to set email alerts
|

Visual priming of two-step motion sequences

Abstract: Perception of an ambiguous apparent motion is influenced by the immediately preceding motion. In positive priming, when an observer is primed with a slow-pace (1–3 Hz) sequence of motion frames depicting unidirectional drift (e.g., Right–Right–Right–Right), subsequent sequences of ambiguous frames are often perceived to continue moving in the primed direction (illusory Right–Right …). Furthermore, priming an observer with a slow-pace sequence of rebounding apparent motion frames that alt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 28 publications
0
1
0
Order By: Relevance
“…Perception of simple apparent motion direction has previously been thought to be influenced by low‐level physical changes (e.g., contrast, frequency and speed; Davidenko et al, 2022; Watson, 1986; Zhang et al, 2012). Our findings further indicated that high‐level visual information (i.e., biological signals) can also influence the perceived direction of apparent motion.…”
Section: Discussionmentioning
confidence: 99%
“…Perception of simple apparent motion direction has previously been thought to be influenced by low‐level physical changes (e.g., contrast, frequency and speed; Davidenko et al, 2022; Watson, 1986; Zhang et al, 2012). Our findings further indicated that high‐level visual information (i.e., biological signals) can also influence the perceived direction of apparent motion.…”
Section: Discussionmentioning
confidence: 99%